2001
DOI: 10.1007/s00276-001-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral pedicle anatomy in relation to pedicle screw fixation: a cadaver study

Abstract: New techniques to stabilize and correct the thoracic and lumbar spine have been developed in recent years. In view of the wide variety and complexity of fixation devices, the optimum configuration of spinal instrumentation systems needs to be defined. Linear and angular measurements of both vertebral pedicles were made in ten complete thoracic and lumbar cadaveric spines using callipers and a goniometer. The vertical interpedicular distance gradually increased along the spine up to L5. The transverse interpedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 19 publications
8
32
1
1
Order By: Relevance
“…In this study, similar to other studies, TOPD was shown a decreasing dimension from T1-T4 followed by an increasing dimension from T5-T8 1,9,12,14,15,18) . Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, similar to other studies, TOPD was shown a decreasing dimension from T1-T4 followed by an increasing dimension from T5-T8 1,9,12,14,15,18) . Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The risk from the pedicle violation of the screw is higher because the thoracic pedicles are smaller and variable compared with lumbar pedicles. It is hardly surprising that the rate of reported pedicle wall perforation in the thoracic spine ranges from 15.9 to 54.7% 1,8,13,21) . Despite the difficulty in precise instrumentation, there are few reports on analysis of the thoracic pedicle morphometry.…”
Section: Discussionmentioning
confidence: 99%
“…α and β axes are coplanar and the intersection of these two axes is a pivot point of needle guide. According to the study of Chaynes [8], the transverse pedicular angle of spinal bone is ≦ 31˚ and the sagittal pedicular angle is ≦ 25˚ to a median position. Therefore, the angle of needle insertion is about 30 degrees [8] to a median position.…”
Section: Spine Punctures Assistance Robotic Systemmentioning
confidence: 99%
“…In the upper thoracic region, due to the anterior curvature, the main part of the compressive force is transmitted through the anterior column formed vertebral body and intervertebral disc, with resulting increased stress (3) . The compressive force in the lower thoracic region is transmitted through two parallel columns, one anterior and one posterior formed by successive articulations of laminae with each other (4) .In recent years, there have been considerable developments in instrumentation designed to stabilize and correct the thoracic spine (5) . Anterior inter body fusion, in association with a variety of methods to stabilize both the implant and motion segment, has increased in popularity.…”
Section: Introductionmentioning
confidence: 99%